Reflections on visual language in the process of artifact formgiving - SIlveira, Nathalie Barros da Mota; Cavalcante, Virginia Pereira (DAT Journal, 2021)
This paper presents the academic and professional paths taken by the author, together with the results and reflections concerning the research he carried out. Starting from the studies which began with the Project and Collection “Olhar, Olhares” (“Look, Looks”) in 2002 and continuing until the present moment, other inquiries on the education and role of the designer in society take place; all the stages that led to the SEE BEYOND method (2016), created during his doctorate, are described. This method has also triggered and oriented other views on undergraduate education and product development in the field of fashion, in a dialogue between Design and Neuroscience.